Secondary Membranous Nephropathy. A Narrative Review - Moroni, Gabriella; Ponticelli, Claudio (Frontiers in Medicine, 2020)
Membranous nephropathy (MN) is a common cause of proteinuria and nephrotic syndrome all over the world. It can be subdivided into primary and secondary forms. Primary form is an autoimmune disease clinically characterized by nephrotic syndrome and slow progression. It accounts for approximately 70% cases of MN. In the remaining cases MN may be secondary to well defined causes, including infections, drugs, cancer, or autoimmune diseases, such as systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), urticarial vasculitis, sarcoidosis, thyroiditis, Sjogren syndrome, systemic sclerosis or ankylosing spondylitis. The clinical presentation is similar in primary and secondary MN. However, the outcome may be different, being often related to that of the original disease in secondary MN. Also, the treatment may be different, being targeted to the etiologic cause in secondary MN. Thus, the differential diagnosis between primary and secondary MN is critical and should be based not only on history and clinical features of the patient but also on immunofluorescence and electron microscopy analysis of renal biopsy as well as on the research of circulating antibodies. The identification of the pathologic events underlying a secondary MN is of paramount importance, since the eradication of the etiologic factors may be followed by remission or definitive cure of MN. In this review we report the main diseases and drugs responsible of secondary MN, the outcome and the pathogenesis of renal disease in different settings and the possible treatments.